Determination of sex from the talus of Indian Population using morphometrical analysis - DR. SHARON SINDHURA SADANANDAM, M. D,; DR. RAJA REDDY GANGAM, M. D, (International Journal of Pharma and Bio Sciences, 2016)
The determination of sex from an adult human skeleton is a fundamental task for forensic and physical anthropologists. Sex determination from skeletal remains may be done through morphologic (non-metric) or metric analyses. The talus has been shown to be useful for human identification as it is often well preserved during excavations and easily distinguished even in a fragmentary state due to its unique morphology. The aim of the present study is determination of sex from the talus of Indian population using morphometrical analysis. Therefore, the present study was undertaken to study talus for various morphological features such as length, width, height, neck length and neck breadth of the talus. In this study five variables of right and left talus were taken with the intention to show the differences in variable measurements of both sides and determine the sex. We have tried to determine the sex of the talus (162), taking into consideration the variable measurements of the 21 (seven females and 14 males) tali where the sex of the bone was known. The mean for all the variables of the tali studied viz., length, width, height, its neck length and breadth of the male right and left tali are more than those of the female right and left tali on either side. For the determination of the sex the literature available was not adequate, hence, we have compared tali of known sex and evaluated the results with the bones of unknown sex and tried to establish the sex of the bone. As per the variables in most cases (length, width, height, neck length, neck breadth) the sex of the bone identification was up to 75-92%.